A highly sensitive detection of carbendazim pesticide in food based on the upconversion-MnO2 luminescent resonance energy transfer biosensor. (1st July 2021) - Ouyang, Qin; Wang, Li; Ahmad, Waqas; Rong, Yawen; Li, Huanhuan; Hu, Yuqian; Chen, Quansheng
Highlights: UCNPs were synthesized with good water solubility and optical properties. The novel CBZ detection sensor via the LRET between UCNPs and MnO2 was developed. Application in food samples of this nanosensor has achieved good results. Under the optimized condition, a 0.05 ng·mL −1 LOD was achieved. Abstract: Carbendazim (CBZ) pesticide residues in food products have become a growing concern in recent years. Herein, a sensitive biosensor for detecting CBZ was developed based on luminescent resonance energy transfer (LRET) from aptamer labeled upconversion nanoparticles (UCNPs, donor) to manganese dioxide (MnO2, acceptor) nanosheets. The strong overlap between the absorption spectrum of MnO2 and the UCNPs fluorescence emission allowed the luminescence quenching. With the addition of CBZ, it tended to bind with specific aptamers, which culminated in the UCNPs-aptamer dropping off MnO2 nanosheets and restoring the fluorescence. A linear calibration plot between logarithmic CBZ concentration and fluorescence intensity was acquired in the range of 0.1–5000 ng·mL −1, with a limit of detection 0.05 ng·mL −1, indicating that the UCNPs- MnO2 aptasensor is a rapid, sensitive and specific quantitative detection platform for CBZ. Furthermore, the precision and accuracy of the developed LRET biosensor was validated by HPLC method with no significant differences.